Effects of hip abducted position during eccentric-only resistance exercise on acute changes in passive stiffness of the biarticular hamstring muscles - Raki Kawama; Katsuki Takahashi; Ryo Nobukawa; Taku Wakahara (PLoS ONE, 2025)
Recent studies have revealed that eccentric-only resistance exercise has the potential to acutely decrease passive stiffness of some biarticular hamstring muscles. The biarticular hamstring muscles are hip adductors and thus are greatly lengthened in the hip abducted position. Based on these findings, this study aimed to investigate whether eccentric-only resistance exercise in hip abducted positions, rather than in the hip-neutral position, induces a greater acute decrease in the passive stiffness of the biarticular hamstring muscles. Eleven participants performed eccentric-only knee flexions with different hip abducted positions (0° abduction [ABD0]; 20° abduction [ABD20]; 40° abduction [ABD40]) on separate days. Maximal joint range of motion, passive torque, shear moduli of the biarticular hamstring muscles, and maximal isometric torque were measured before and 5 min after completing each exercise. The shear moduli of the biceps femoris long head and semitendinosus were significantly lower at 5 min post-exercise than at pre-exercise in all hip joint positions. In the semimembranosus, the shear modulus was significantly lower at 5 min post-exercise than at pre-exercise at ABD0 and ABD20, but not at ABD40. In the three muscles, there were no significant differences in the changes in the shear moduli at 5 min post-exercise among the hip abducted positions. These findings suggest that eccentric-only resistance exercise in hip abducted positions does not necessarily amplify the acute decrease in the passive stiffness of the biarticular hamstring muscles and may even attenuate the decrease in stiffness of a specific muscle.